Disagreement, boundaries and manners and solutions with Sharia text - Muhammad Asif Haroon; Muhammad Hammad Atta (jihat-ul-islam, 2023)
Any society exists with human beings. People living in society have different ways of thinking, understanding, evaluating, knowing, seeing, and judging based on cognitive and intellectual differences. It is natural for them to differ in their opinion on anything based on this difference. Every day, we witness that the opinions of people in the same place and doing the same work sometimes differ. Difference of opinion is a natural elixir but the question is, can we impose our opinion on others? Are there any limits and restrictions to the difference of opinions or not? What manners should be kept in mind in when we make a difference of opinion? What are our social attitudes towards differences of opinion and what guidance does Islam give us in this regard? In this paper, an attempt will be made to answer these questions through the narrative method of research.